Roadmap to rewards (the triple jump step phase repair flowchart) - Schexnayder, B. (Techniques Magazine, 2024)
The chart provided is designed to work as a roadmap in this search. It provides the coach a system of analysis and diagnosis for step phase problems by beginning at the step phase problems by beginning at the step phase takeoff and working beack in true cause-and-effect methodology. The chart uses a flowchart apporach to this diagnostic procedure, requiring certain evaluations to be made and video checkpoints to be analyzed as the roots of these problems are unearthed.